Pharmacological activity of composition on the base of dihydroquercertin and lipoic acid - I. S. Ivanov; A. V. Sidekhmenova; A. M. Anischenko; O. I. Aliyev; N. A. Tyukavkina; M. B. Plotnikov (Бюллетень сибирской медицины, 2011)
The purpose of this investigation is to the estimate influence of composition dihydroquercertin and lipoic acid on lymphatic flow, capillary filtration and blood viscosity in comparison with effects of individual components. Lymphokinetic activity of dihydroquercertin was detected. Capillary-protective effect, but in less degree lymphokinetic and hemorheologic ones of composition are higher than the effect of its separate components.